Are Malawi’s maize and soya trade restrictions causing more harm than good? A summary of evidence and practical alternatives - Edelman, Brent; Baulch, Bob (International Food Policy Research Institute, 2016)
Since the early 2000s, the government of Malawi has used trade restrictions, export bans in particular, to control trade flows for maize and soya, among other crops. Maize export bans, justified in the name of national food security, have been in place more or less continuously since 2005, with the ban lifted temporarily in 2007-08 and 2009-11. Export bans on soya, used to benefit domestic vegetable oil processors and the poultry industry in the form of lower input prices, were imposed several times for a few months at a time between 2010 and 2012. In 2013, government scrapped soya export bans as a trade policy tool, but since 2015 has explored other measures to limit soya exports, including an export levy and a mandate that all soya exports be processed through a single trading company.